Community of insecurity SADC's struggle for peace and security in Southern Africa - Nathan, Laurie (The International political economy of new regionalisms series, 2012)
Exploring the formation, evolution and effectiveness of the regional security arrangements of the Southern African Development Community (SADC), the author examines a number of vital and troubling questions: Why has SADC struggled to establish a viable security regime? Why has it been unable to engage in successful peacemaking?